Structure of the human 3-methyladenine DNA glycosylase gene and localization close to the 16p telomere. - Vickers, M A (1993)
We recently reported the presence of four genes lying between the human alpha-globin gene cluster and the telomere of the short arm of chromosome 16 (16p). We now report that one of these genes encodes 3-methyladenine DNA glycosylase, an enzyme important in the repair of DNA after damage by alkylating agents. The gene comprises five exons, representation of which differs in independently isolated cDNA clones. Although the gene is widely expressed, the abundance of its mRNA is considerably higher in a colon adenocarcinoma cell line (HT29) than in other cell lines that were tested. The major positive erythroid-specific regulatory element controlling alpha-globin gene expression lies equidistant between the promoters of the alpha-globin genes and the 3-methyladenine DNA glycosylase gene. Interestingly, in contrast to the alpha-globin genes, expression of the 3-methyladenine DNA glycosylase gene is not influenced by the regulatory element in the human erythroleukemia cell line K562.